The Effect of Fuel Injection Duration on Exaust Gas Emissions of a 4-Stroke Engine 113.68 CC Using Bioethanol Fuel - Iqbal Zulfikar; Akhmad Nurdin; Angger Bagus Prasetiyo; Bambang Irawan (Jurnal Pendidikan Teknik Mesin, 2025)
In Indonesia, the number of motor vehicles using fuel as an energy source is rising quickly. The government has developed renewable energy to reduce fuel consumption because, according to the Downstream Oil and Gas Regulatory Agency (BPH Migas), the consumption of gasoline-type fuels in 2017 was 1,858,875 L/Quarter. Determining the impact of using bioethanol with different injection times on exhaust gas emissions was the aim of this study. Bioethanol is an environmentally friendly alternative fuel for cars that uses less fuel. It is a renewable energy source made from vegetable sources. Variations in fuel injection duration and exhaust gas emission are the main subjects of this study. With no modifications to compression, the engine operates under standard conditions. A gas analyzer and engine speeds of 1500, 2000, 3000, 4000, and 5000 Rpm were used in the study. According to the study's findings, the amount of CO exhaust gas dropped. At 5000 RPM for 4 ms, the lowest CO in bioethanol fuel is 1.21%. With bioethanol fuel, the amount of HC exhaust gas emissions has dropped. 710 ppm at 3000 Rpm for 4 ms is the lowest HC level. When using bioethanol as fuel, the amount of CO2 emissions rises. The maximum CO2 concentration is 6.50% at 5000 RPM for 4 ms. The maximum amount of O2 emissions from bioethanol fuel is recorded at 1500 RPM for 4 ms.